2012
DOI: 10.1165/rcmb.2010-0506oc
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1, the Unfolded Protein Response, and Persistent Inflammation

Abstract: Endothelin-1 is a potent vasoactive peptide that occurs in chronically high levels in humans with pulmonary hypertension and in animal models of the disease. Recently, the unfolded protein response was implicated in a variety of diseases, including pulmonary hypertension. In addition, evidence is increasing for pathological, persistent inflammation in the pathobiology of this disease. We investigated whether endothelin-1 might engage the unfolded protein response and thus link inflammation and the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 44 publications
4
57
0
3
Order By: Relevance
“…Accordingly, we chose salubrinal, a cell stress protectant, to modulate the unfolded protein response toward a survival phenotype, away from a proapoptotic phenotype (control node 1). This was based on our recent observations that salubrinal protects against MCTinduced pneumotoxicity and pulmonary vascular remodeling (23). Salubrinal, when coadministered with MCT and then twice per week thereafter for 4 weeks, significantly reduced BALT size and number and largely prevented autoantibody formation in rats ( Figure 6A).…”
Section: Strategies Aimed At Diminution Of Balt Biology Prevent and Rmentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, we chose salubrinal, a cell stress protectant, to modulate the unfolded protein response toward a survival phenotype, away from a proapoptotic phenotype (control node 1). This was based on our recent observations that salubrinal protects against MCTinduced pneumotoxicity and pulmonary vascular remodeling (23). Salubrinal, when coadministered with MCT and then twice per week thereafter for 4 weeks, significantly reduced BALT size and number and largely prevented autoantibody formation in rats ( Figure 6A).…”
Section: Strategies Aimed At Diminution Of Balt Biology Prevent and Rmentioning
confidence: 84%
“…MCT is a broad pneumotoxin that causes lung cell apoptosis, airway cytokine flux, airway constriction, and decreased respiratory compliance. We recently found that MCT causes a robust activation of the unfolded protein response and CCAAT/enhancer-binding protein homologous protein (CHOP)-mediated apoptosis (23) in bronchial epithelium within 48 hours of MCT administration. Salubrinal-mediated unfolded protein response modulation reduced the number and extent of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another study linked endothelin with the unfolded protein response, mitochondrial dysfunction, and inflammation (117).…”
Section: Elastase Activitymentioning
confidence: 99%
“…The molecular phenotype of PAH-PASMC persists even in vitro (where the potential primary triggers like circulating factors or paracrine signals are absent), suggesting that there may be positively reinforcing feedback loops that sustain the 21 and STAT3 activation 22 …”
Section: Metabolic Remodeling In Pah Vascular Cells and Itsmentioning
confidence: 99%
“…115 Increased Endothelin-1 signaling, a well-studied pathway in PAH, was also recently shown to induce ER stress. 21 Inhibition of ER stress by the small molecule chemical chaperone phenylbutyrate reverses the decrease in mitochondrial calcium and the PDH inhibition and normalizes the cellular phenotype of PAH, whereas it prevents and reverses PAH in rodent models. 75 ER stress in PAH-PASMCs has also been linked to increased production of cytokines like interleukin-6 and chemokine (C-C motif) ligand 2/ mast cell proteinase-1, Figure 4.…”
mentioning
confidence: 99%